Body Mass Index (BMI), Pregnancy Readiness, and Belief in Healthy Pregnancy - Sriyanti, Chris; Ferina, Ferina (Journal of Midwifery, 2024)
Before planning a pregnancy, women should prepare themselves optimally in physical, psychological, and social aspects. This study aims to analyze the relationship between BMI and readiness for pregnancy and belief in having a healthy pregnancy. This research is an analytical study using a cross-sectional method with 196 respondents. Bivariate analysis was conducted using the chi-square test, which revealed no significant relationship between BMI and readiness for pregnancy or belief in a healthy pregnancy (p-value >0.05). However, there was a significant relationship between readiness for pregnancy and the belief in a healthy pregnancy (p-value=0.000). BMI is not the primary factor associated with readiness for pregnancy or the belief in having a healthy pregnancy. This may be due to other factors exerting a stronger influence on readiness and belief in a healthy pregnancy. Readiness for pregnancy can enhance positive perceptions of a woman’s ability to undergo a healthy pregnancy and influence better behavior and decision-making for a healthy lifestyle during pregnancy. Comprehensive interventions during the preconception period need to be developed to prepare women planning for pregnancy so they ready and confident in their ability to undergo a healthy pregnancy